Mechanistic investigation into phenol oxidation by IBX elucidated by DFT calculations. Issue 6 (29th January 2020) - Kaur, Amritpal; Ariafard, Alireza
Abstract : Density functional theory (DFT) at the SMD/M06-2X/def2-TZVP//SMD/M06-2X/LANL2DZ(d), 6-31G(d) level was used to explore the regioselective double oxidation of phenols by a hypervalent iodine(v ) reagent (IBX) to give o -quinones. Abstract : Density functional theory (DFT) at the SMD/M06-2X/def2-TZVP//SMD/M06-2X/LANL2DZ(d), 6-31G(d) level was used to explore the regioselective double oxidation of phenols by a hypervalent iodine(v ) reagent (IBX) to give o -quinones. The oxidative dearomatization commences with the ligand exchange between IBX and phenol, yielding a phenolate complex, followed by the first redox process, which reduces iodine(v ) to iodine(iii ). Both the processes (the ligand exchange and the first redox reaction) were found to be mediated by a less stable isomer of iodine(v ) species. We found that although the first redox process preferentially proceeds via an associative pathway, an electron withdrawing substituent on the phenol ring decreases its accessibility. The inspection of the electronic structure of the redox transition state indicates that the phenolate involved in the iodine(v ) reduction has some phenoxenium character. The intrinsic stability of a phenoxenium ion is calculated to be highly sensitive to the substituent on the phenol ring. Since the electron withdrawing substituents considerably decrease the stability of the phenoxenium, they render the iodine(v ) to iodine(iii ) reduction energy consuming. Once the first redox step has completed, a catechol-iodine(iii ) complex is formed, from which the second redox process produces the final o -quinone product via a carboxylate-assisted transition structure. This transition structure gains stability by hydrogen bond interaction between the catechol OH and carboxylate group. Such an interaction results in the phenolate not having any phenoxenium character in the transition structure, thus making the activation barrier to the second redox step independent from the substituent on the phenol ring.